Preferensi setting pendukung aktivitas gen z di ruang terbuka publik, studi kasus: Alun-alun Kidul Yogyakarta - Alif Faricha Almadina; Syam Rachma Marcillia (JURNAL ARSITEKTUR PENDAPA, 2023)
Z-generations are adolescents and youths in the development phase of interpersonal competence. This capability can fill through leisure activities which are interacting with peers. Public open space become one of Z generation’s favorite destinations for doing leisure activities. Z-generation activities are formed by setting in public open spaces. This study aims to determine the setting preferences supporting Z-generation activities in public open spaces. The research focus is located at Alun-alun Kidul, a public open space that provides various activities. The method used was questionnaires and interviews with purposive sampling. Results of the study showed that Z generations preferred doing culinarian and having some conversations. Z generations tend to be close with friends while in Alun-alun Kidul. The preferred setting for culinarian and gatherings is the setting that provides comfortable sitting zones, such as a lesehan mat, plastic chair, and grass area.